Physical, chemical, nutritional and antinutritional characterization of fresh peels of yellow pitaya (Selenicereus megalanthus) and red pitaya (Hylocereus costaricensis) and their flours - Morais, Daphynni Carolinne; Alves, Vânia Maria; Asquieri, Eduardo; de Souza, Adriana; Damiani, Clarissa (Revista Ciência Agronômica, 2021)
The consumption of fruits has been growing worldwide due to the exigence of consumers for healthy eating habits, generating a significant volume of agro-industrial waste such as peels. The objectives of this work were the physical, chemical, nutritional, and antinutritional characterization of fresh peels of yellow and red pitaya, as well as the production, characterization, and study of technological properties of these flours of peels. The humidity values obtained for the peels were between 88.56% and 91.18% and between 5.25% and 9.62% for the flours. For water activity, the peels had values of 0.94 and the flours between 0.35 and 0.52, showing that flours are more indicated to develop new products, such as bread and cookies, besides presenting higher protein content and low lipid content. The flours present glucose, maltose, xylose, fructose as the main sugars, high fiber content, minerals, and antioxidant capacity. It was not detected the presence of cyanogenic compounds, condensed and hydrolyzed tannins. It was concluded that the flours presented an excellent alternative as an ingredient to be incorporated in food products, in which the yellow pitaya flour stands out compared with red pitaya flour regarding contents of proteins, ashes, potassium, phosphorus, zinc, vitamin C, absorption index in oil, and the red pitaya flour stands out in calcium, manganese, copper, absorption index and solubility in water, absorption index in milk.